Juridical Review of the Settlement of Khalwat Cases by the Adat Courts in Aceh - Jalaluddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Progressive law enforcement in the settlement of cases in Indonesia can be found in law enforcement in Aceh, namely through the stipulation of the Governor of Aceh Regulation Number 9 of 2008 concerning Fostering Traditional Life and Customs. There are 18 cases/disputes that are the scope of handling, including Khalwat. Various efforts have been made to absorb the law that lives in society, none other than to achieve the goal of law in orderly society. Conceptions of law that conflict with the diversity of society can be seen as a failure to implement effective and efficient law. The competence of a decision-making official is a separate issue to pay attention to. Likewise the mechanism is implemented with good intentions, but whether it will have a good impact cannot be generalized in general. Given the competencies and insights that depart from different understandings, this can have a significant impact on the decisions taken. The role of community leaders as customary judges is a dilemmatic issue in law enforcement related to khalwat. The point of view of khalwat acts that are not only about violating the law, but also about moral violations is an important issue that must be properly processed.